Implementation of Deep Learning Approach of Pancasila Education to Increase Critical Thinking Students - Ali Miftakhu Rosyad; Najeem Olawale Adelakun (International Journal of Science Education and Cultural Studies, 2025)
Critical thinking is essential in 21st-century higher education, yet traditional Pancasila education often fails to develop this competency. This mixed-method study investigated how deep learning approaches pedagogical strategies emphasizing mastery, problem-solving, and disposition development enhance critical thinking among 120 undergraduate students at Universitas Wiralodra. Students were divided into experimental groups receiving deep learning instruction and control groups receiving traditional methods. Results showed experimental group students achieved substantially higher critical thinking scores with large effect sizes (Cohen's d=1.66, p<0.001). Qualitative findings revealed that problem-based learning, Socratic dialogue, and reflective practices enhanced students' analytical abilities and engagement. The main contribution of this study is demonstrating that contextualized deep learning pedagogies can effectively transform civic education from knowledge transmission to critical competency development in Indonesian higher education settings. Practically, this research provides evidence-based implementation frameworks for educators seeking to enhance critical thinking through authentic problem-solving and collaborative inquiry in Pancasila education.